Alternating Unilateral Versus Bilateral Injections of Botulinum Toxin for the Treatment of Adductor Spasmodic Dysphonia. (April 2021) - Lee, Seung Jin; Kang, Min Seok; Choi, Hong-Shik; Lim, Jae-Yol
Objective: This study aimed to compare the long-term efficacy, durability, and dose and interval stability between alternating unilateral and bilateral injections of botulinum neurotoxin type A for the treatment of adductor spasmodic dysphonia. Study Design: Retrospective cohort study. Setting: Academic tertiary medical center. Methods: A total of 137 patients (105 alternating unilateral and 32 bilateral injections) who were administered ≥5 injections of botulinum neurotoxin type A were included in this study. The mean dosage change, dose adjustment ratio (number of dose increases/total number of injections), and stability of treatment responses were compared between the alternating unilateral and bilateral injection groups. Results: Long-term changes in the mean dosages for alternating unilateral (mean ± SD, –0.010 ± 0.048 IU) and bilateral (–0.042 ± 0.142 IU) injections did not differ between groups ( P = .225), suggesting that both methods follow a decreasing dosing trend over time. The dose adjustment ratio also did not differ between groups ( P = .077), although a longer average treatment interval ( P < .001) and duration of hoarse voice ( P = .045) were found in the bilateral injection group. The proportion of stable patients who did not increase injection dose and had regular follow-up did not differ between the groups. Conclusion: Both alternating unilateral and bilateral injection methods showed a long-term decreasing dosing trend, with comparable levels of efficacy, durability, and stability for treating adductor spasmodic dysphonia. Our findings indicate that alternating unilateral injections can be routinely performed with fewer side effects, albeit at shorter treatment intervals, than bilateral injections.